Anatomic changes in head and neck intensity-modulated proton therapy: Comparison between robust optimization and online adaptation. (June 2021) - Lalonde, Arthur; Bobić, Mislav; Winey, Brian; Verburg, Joost; Sharp, Gregory C.; Paganetti, Harald
Highlights: A novel online adaptive strategy was compared to two robust optimization methods. Daily CBCT images were used to introduce realistic setup and anatomical variations. Robust optimization achieved adequate target coverage in up to 8/10 patients. Online adaptation yielded adequate target coverage in all patients. Online adaptation reduced the dose to most OARs compared to robust methods. Abstract: Background/purpose: Setup variations and anatomical changes can severely affect the quality of head and neck intensity-modulated proton therapy (IMPT) treatments. The impact of these changes can be alleviated by increasing the plan's robustness a priori, or by adapting the plan online. This work compares these approaches in the context of head and neck IMPT. Materials/methods: A representative cohort of 10 head and neck squamous cell carcinoma (HNSCC) patients with daily cone-beam computed tomography (CBCT) was evaluated. For each patient, three IMPT plans were created: 1- a classical robust optimization (cRO) plan optimized on the planning CT, 2- an anatomical robust optimization (aRO) plan additionally including the two first daily CBCTs and 3- a plan optimized without robustness constraints, but online-adapted (OA) daily, using a constrained spot intensity re-optimization technique only. Results: The cumulative dose following OA fulfilled the clinical objective of both the high-risk and low-risk clinical target volumes (CTV) coverage in all 10 patients, compared to 8 for aRO and 4 for cRO. aRO did not significantly increase the dose to most organs at risk compared to cRO, although the integral dose was higher. OA significantly reduced the integral dose to healthy tissues compared to both robust methods, while providing equivalent or superior target coverage. Conclusion: Using a simple spot intensity re-optimization, daily OA can achieve superior target coverage and lower dose to organs at risk than robust optimization methods.